The clinical study on the cased of Herpes Zoster Treated with Korean Oriental Medicine - Seong-Wook Kim (Korean Pharmacopuncture Institute, 2001)
Objective : These case study were made to evaluate and observe the treatment for the Herpes-Zoster through the korean oriental medicine. Method : Clinical observation and analysis about 4 cases of Herpes-zoster including the Ramsay's-hunt syndrome had been done the patients of the Sang-Ji Oriental Medicine Hospital. These cases were mainly treated with oriental medicine using the Herb medication, Korean Bee-Venom therapy, Acupuncture and Electro-acupuncture therapy. Acupuncture technic was mainly used Sa-Am acupuncture(Four needle technique). Result : After treatment, all of cases were completely cured without any complication. Conclusion : Based on the clinical results, Korean Oriental Medicine is believed to be effective for treating Herpes-zoster, and further studies should be conducted to provide more valuable information.